(untitled) (Italiano LinguaDue, 2019)
Come si presenta la scuola multiculturale italiana? Com’è cambiata in questi anni? Quali sono i riferimenti di legge e le azioni più efficaci? A partire da queste e altre domande, il Documento, elaborato nell’ambito del progetto europeo Erasmus plus IRIS (Investigating and Reconstructing the Individual Language Stories), delinea il ritratto della scuola multiculturale e ne racconta i passaggi. Gli aspetti trattati riguardano: i dati e le tendenze, la normativa, le criticità e i punti di forza; alcune buone pratiche sull’insegnamento dell’italiano L2 e la valorizzazione della diversità linguistica condotte a livello nazionale. Languages, standards, practices What are Italian multicultural schools like? How have they changed in recent years? What laws and actions are most effective? Starting from these and other questions, this document, part of the European project Erasmus plus IRIS (Investigating and Reconstructing the Individual Language Stories), outlines the portrait of the multicultural school and its evolution. The aspects dealt with include: data and trends, regulations, critical issues and strengths; some good practices in Italian L2 teaching and the promotion of linguistic diversity conducted at national level.